Paenibacillus wound infection in a pediatric trauma patient - Sindhu V. Mannava; James DeCou; Daniel J. Watkins; Teri Crumb; Emily Pardington; Elliot C. Pennington (Elsevier, 2022)
We report a case of Paenibacillus wound infection in an immunocompetent and otherwise healthy nine-year-old boy who sustained a laceration following an all-terrain vehicle crash. During his course, he failed non-operative management and required multiple wound washouts and a thirty-six-day course of antibiotics. While this pathogen is most known for causing honeybee disease known as American Foulbrood (AFB), Paenibacillus has been implicated in a handful of human wound complications in the post-traumatic setting. This is a rare, opportunistic bacteria that is resistant to many commonly prescribed antibiotics. Less than twenty cases of human Paenibacillus wound infections have been reported in the literature and when they do occur, they often affect immunocompromised patients or those with chronic medical co-morbidities. In the last ten years, there have been four case reports of neonatal sepsis caused by this pathogen. This appears to be the first pediatric Paenibacillus wound infection reported.